2008
DOI: 10.1007/s00330-008-0878-0
|View full text |Cite
|
Sign up to set email alerts
|

Observer variability in screen-film mammography versus full-field digital mammography with soft-copy reading

Abstract: Full-field digital mammography (FFDM) with soft-copy reading is more complex than screen-film mammography (SFM) with hard-copy reading. The aim of this study was to compare inter- and intraobserver variability in SFM versus FFDM of paired mammograms from a breast cancer screening program. Six radiologists interpreted mammograms of 232 cases obtained with both techniques, including 46 cancers, 88 benign lesions, and 98 normals. Image interpretation included BI-RADS categories. A case consisted of standard two-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…The success of screening mammography depends on the detection of small, subtle non-palpable cancers which may be a very difficult task. Consequently, inter-observer and intra-observer variability that may be affected by many factors such as case difficulty, radiologist’s experience, varying practices and others, is a great challenge in mammographic screening and has been shown to be a great problem for SFM as well as FFDM [4, 5]. In a nationwide mammography screening programme using independent double reading, a total of 23 % of the screening-detected cancers had a discordant interpretation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The success of screening mammography depends on the detection of small, subtle non-palpable cancers which may be a very difficult task. Consequently, inter-observer and intra-observer variability that may be affected by many factors such as case difficulty, radiologist’s experience, varying practices and others, is a great challenge in mammographic screening and has been shown to be a great problem for SFM as well as FFDM [4, 5]. In a nationwide mammography screening programme using independent double reading, a total of 23 % of the screening-detected cancers had a discordant interpretation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies were written in German with no English translation [24, 25] and thus excluded as well. Two studies evaluated only intraobserver agreement [26, 27], one study compared observer responses to a study-defined gold standard [18], one reported only mean kappas [30], one measured agreement between crainocaudal and mediolateral oblique view ratings [22] and three measured agreement between film screen and digital mammogram ratings [17, 28,29]. Lastly, we excluded two additional studies because agreement was not measured on BI-RADS terminology and/or final assessment categories.…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear whether this affected their performance. Per Skaane et al 16 found considerable intra and inter observer variation in their examination of screen film reporting and full field digital mammography. They interpret their findings as indicating the need for proper training for soft copy reading.…”
Section: Discussionmentioning
confidence: 99%